2020
DOI: 10.1016/j.jobcr.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cleaning effectiveness of single rotary file OneShape and reciprocating F2 Protaper with Protaper Universal sequence: A SEM analysis

Abstract: This in vitro study intend to compare the cleaning effectiveness of Protaper universal sequence with reciprocating F2 Protaper and single rotary file One shape. Materials and method: 30 extracted human 1st mandibular molars were chosen for the analysis. Three NiTi file systems were used for mechanical preparation, ProTaper full sequence in rotary motion, single F2 Protaper file used in reciprocating motion, and One shape single file used in a circular motion. Irrigation was carried out after each instrument us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…With the same purpose in mandibular incisors, De-Deus et al 22 , revealed that better cleaning was observed when preparation was performed with sequential instruments. Similar results were also highlighted in another study, although performed on molars, the differences occurred when the canals were also prepared in sequential mode 23 .…”
Section: Discussionsupporting
confidence: 86%
“…With the same purpose in mandibular incisors, De-Deus et al 22 , revealed that better cleaning was observed when preparation was performed with sequential instruments. Similar results were also highlighted in another study, although performed on molars, the differences occurred when the canals were also prepared in sequential mode 23 .…”
Section: Discussionsupporting
confidence: 86%
“…Although the null hypothesis of the current study was maintained, canal walls were noticed to be cleaner after using file with reciprocation in comparison to rotatory files, but this difference was not statistically significant in agreement with some authors (26,27) . However, in another study, when comparing protaper full sequence as rotating file to protaper F2 as reciprocating file, protaper full sequence demonstrated better cleaning ability and smear layer removal (28) .…”
Section: Discussionmentioning
confidence: 92%
“…However, there is no agreement on how to standardize debris and smear layer measurements. In this research, micrographs at higher magnifications 1000X were used to evaluate the smear layer on the root surface and dentinal tubules, whereas 200X magnification was utilized to evaluate the debris layer on the root canal surfaces [4] [24].…”
Section: Discussionmentioning
confidence: 99%